GENE-15. TARGETING OF EPENDYMOMA AS INFORMED BY ONCOGENIC 3D GENOME ORGANIZATION. (11th November 2019) - Okonechnikov, Konstantin; Hübner, Jens-Martin; Chapman, Owen; Chakraborty, Abhijit; Bump, Rosalind; Chandran, Sahaana; Kraft, Katerina; Acuna Hidalgo, Rocio; Mundlos, Stefan; Coufal, Nicole; Levy, Michael; Crawford, John; et al.
Abstract: By profiling enhancers in primary ependymoma tumors, we have recently identified putative oncogenes, molecular targets, and functional pathways. Inhibition of selected targets diminished the proliferation of patient-derived neurospheres and increased survival in mouse models of ependymoma. While enhancers frequently regulate the nearest gene, unambiguous identification of enhancer target genes remains to be a challenge in the absence of chromosome conformation information. Consequently, we have now used HiC to map the 3-dimensional organization of tumor chromatin in the two most common and aggressive ependymoma subgroups: posterior fossa group A (PF-EPN-A) and supratentorial ependymomas with gene fusions involving the NF-κB subunit gene RELA (ST-EPN-RELA). By an integrative analysis of enhancer and gene expression in the context of the newly derived HiC data, we find that a large amount of the previously predicted enhancer target genes can be confirmed by physical interactions. Importantly, we also identify many new putative tumor-dependency genes activated by long-range promoter-enhancer interactions. Complementary to the analysis of gene-enhancer interactions, we have also leveraged the HiC data for resolving structural rearrangements underlying copy number alterations frequently observed in PF-EPN-A tumors. Especially copy number gains of the 1q arm of chromosome 1 are associated with poor survival. Our preliminary results reveal complex structural variants that underlie 1q gains, which lead to inter-chromosomal rearrangements and affect several genes that potentially contribute to poor survival. We now aim to test the relevance of the novel candidate tumor-dependency genes for tumor cell growth and proliferation in patient derived ependymoma models.